Biological invasion: Long term monitoring of the macroalgal flora of a major European harbor complex. (June 2019) - Verlaque, Marc; Breton, Gérard
Abstract: The marine macroflora of the ports of Le Havre and Antifer have been studied by citizen scientists since the late 1970s. In addition to analysis of the previous results, the field study was extended from 2010 to 2018. A total of 97 and 62 macroalgae were identified, respectively, including 14 NIS (non-indigenous species), the latter number being certainly an underestimate since microscopic species were not exhaustively sought and given the high number of cryptogenic species encountered. No new primary introduction of NIS for the NE Atlantic has been detected since the late 1970s. The origin of NIS and vector(s) of introduction were investigated. For all NIS, the donor region is the Indo-Pacific. Two likely vectors have been identified: maritime traffic for earlier introductions, and shellfish imports for more recent ones. The role of these ports and maritime traffic in the processes of introduction is discussed. Highlights: A 50-year-old citizen science program. Le Havre-Antifer: 14 non-indigenous species of macroalgae. No new primary introduction of macroalgae for the NE Atlantic since the late 1970s. Only one donor region for the NIS: the Indo-Pacific Ocean. Only two likely vectors: maritime traffic and shellfish imports.